KEPUASAN PASIEN TENTANG IMPLEMENTASI PROTOKOL KESEHATAN PADA PELAYANAN PIJAT IBU DAN BAYI DI GRIYA SEHAT MOM and BABY KIDS SPA SAMBONGDUKUH JOMBANG: Patient Satisfications about the Implementastion of Health Protocol in Mother and Baby Massage Service at Griya Sehat Mom and Baby Kids Spa Sambongdukuh Jombang - Any Isro'aini; Fera Yuli Setiyaningsih (LPPM - STIKES Pemkab Jombang, 2022)
The Corona virus outbreak (Covid-19) has been declared a global epidemic by the World Health Organization (WHO) since its emergence in December 2019 in Wuhan, China. This virus is known as Corona Virus Diseases or better known as Covid-19. Is a virus that causes infectious diseases that attack the respiratory tract. This pandemic requires us to break the chain of spread of the corona virus, through several ways, including what the government is currently promoting is the health protocol. Midwives as the spearhead of maternal and child health services are one of the promoters of health protocols in providing health services. Maternal and infant massage services provided by midwives in order to provide flexibility of joints and muscles of the body to the mother, as well as to infants can increase sleep frequency, increase weight, and provide comfort. In all these services, health protocols should be implemented according to standards, so that they will provide good safety for mothers, babies as well as midwives who provide services. The purpose of this study was to determine the description of patient satisfaction regarding the implementation of health protocols in maternal and infant massage services at Griya Sehat Mom And Baby Kids Spa Sambongdukuh Jombang. The research design used is cross sectional analytic. The population of all patients and their parents who came to get massage services for mothers and babies who visited Griya Sehat Mom And Baby Kids Spa Sambongdukuh Jombang was 33 people. This research uses Consecutive Sampling technique. The results of this study found that most of the 31 (93.9%) respondents said they were satisfied, 2 (6.1%) respondents said they were somewhat satisfied with the implementation of health protocols for maternal and infant massage services at Griya Sehat Mom and Baby Kids Spa Jombang. . The conclusion of this study is that most of the 31 (93.9%) respondents said they were satisfied with the implementation of health protocols for maternal and infant massage services at Griya Sehat Mom and Baby Kids Spa Jombang.